Analysis of Cohesion and Coherence in Writing Performance of Iranian Intermediate EFL Learners - Sedigheh Samadian; Ahmad Mohseny (Issues in Language Teaching, 2019)
The main concern of this study was to identify Iranian intermediate EFL learners’ problems in cohesion and coherence of writing performance as well as the extent to which they utilized cohesion and coherence in their writing. It is important for EFL and ESL learners the ability to compose a piece of descriptive text. Despite its significance, there is a gap in the literature about how Iranian EFL learners write essays in this genre that this study intends to fill. The research design involved the utilization of mixed research method in addressing the research questions. The study addressed a corpus of 40 intermediate language learners’ descriptive essays, 10 experienced teachers that they were themselves at intermediate level as the questionnaire respondents and four interviewees’ answers from those volunteer experienced teachers. The results of the study revealed lack of cohesion and coherence in the participants’ essays and their writing performance in terms of these two variables was not acceptable. Therefore, the obtained findings, by implication, indicated that they had neither some aspects of cohesive and coherent writing, nor had enough support, practice and feedback on their written text in terms of cohesion and coherence. Some pedagogical implications of this study would be applicable to the language learners’ writing in terms of these two aforementioned variables as well as the results were expected to aid in setting the writing sections of classes for improvement of language learners’ written texts particularly in terms of cohesion and coherence.